Streamlining referrals by establishing a UAE-specific referral algorithm for CVD patients with overlapping COPD: a collaborative effort by cardiologists and pulmonologists - Shehab, Abdulla; Alzaabi, Ashraf; Al Zubaidi, Abdulmajeed; Mahboub, Bassam; Skouri, Hadi; Alhameli, Hamad; El-Tamimi, Hassan; Iqbal, Mohammed Nizam (Frontiers in Cardiovascular Medicine, 2025)
IntroductionConcomitant COPD and CVD are highly prevalent and contribute to increased risk of hospitalizations, morbidity, and mortality, and impose a significant financial burden on healthcare systems. Diagnosis of COPD in patients with comorbid CVD and vice versa is challenging due to an overlap between the risk factors and symptoms of these two conditions. This 8-member task force comprising pulmonologists and cardiologists agreed that in the UAE, while COPD patients suspected of having CVD are promptly referred to cardiology, CVD patients who may potentially also have COPD are often not referred or referred late from cardiology to pulmonology. This gap in identifying CVD patients who may potentially also have COPD must be addressed to facilitate referrals of such patients to pulmonology.Methods and resultsA task force comprising an equal number of cardiologists and pulmonologists met virtually and identified the gaps in current practices for diagnosing patients with comorbid COPD and CVD in the UAE. The task force has proposed an algorithm to expedite the referral of CVD patients suspected of COPD from cardiology to pulmonology.ConclusionImplementing this referral algorithm across all cardiology departments in the UAE can facilitate the diagnosis of COPD in CVD patients, allow timely treatment of COPD, and improve patient outcomes.